2006
DOI: 10.1124/mol.106.022673
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C76, a Novel Cytochrome P450 in Cynomolgus Monkey, Is a Major CYP2C in Liver, Metabolizing Tolbutamide and Testosterone

Abstract: Monkeys are widely used as a primate model to study drug metabolism because they generally show a metabolic pattern similar to humans. However, the paucity of information on cytochrome P450 (P450) genes has hampered a deep understanding of drug metabolism in the monkey. In this study, we report identification of the CYP2C76 cDNA newly identified in cynomolgus monkey and characterization of this CYP2C along with cynomolgus CYP2C20, CYP2C43, and CYP2C75. The CYP2C76 cDNA contains the open reading frame encoding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
198
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 114 publications
(208 citation statements)
references
References 31 publications
10
198
0
Order By: Relevance
“…CYP2C76 cDNA shows only 75-76% sequence identity to human CYP2Cs. CYP2C76 is not orthologous to any human CYPs [20] and is partly responsible for the difference of drug metabolism between cynomolgus macaques and humans [21]. Such species differences also could be explained by functional disparity of the orthologous CYPs between the two species, such as, if an ortholog to human CYP with low (or no) expression and drug-metabolizing activity, for example CYP2C18, shows abundant expression and substantial activity in cynomolgus macaques.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…CYP2C76 cDNA shows only 75-76% sequence identity to human CYP2Cs. CYP2C76 is not orthologous to any human CYPs [20] and is partly responsible for the difference of drug metabolism between cynomolgus macaques and humans [21]. Such species differences also could be explained by functional disparity of the orthologous CYPs between the two species, such as, if an ortholog to human CYP with low (or no) expression and drug-metabolizing activity, for example CYP2C18, shows abundant expression and substantial activity in cynomolgus macaques.…”
mentioning
confidence: 99%
“…All human CYP2Cs exhibit genetic polymorphisms. In particular, some genetic polymorphisms of CYP2C9 and CYP2C19 have been shown to result in toxicity or altered efficacy of drugs in humans.In cynomolgus macaques, which are used to evaluate drug effects and toxicities in preclinical studies of drug development, cDNAs for CYP2C20, CYP2C43, CYP2C75 and CYP2C76 have been identified [9,20]. CYP2C20 cDNA is highly homologous (95%) to human CYP2C8 cDNA, while CYP2C43 and CYP2C75 cDNAs are highly homologous (93-95%) to both human CYP2C9 and CYP2C19 cDNAs.…”
mentioning
confidence: 99%
See 3 more Smart Citations